Levels of information and pharmaco-therapeutical behavior of dentists, 1990 - Battellino, Luis Jose; Bennun, Fernando Ruben (Revista de Saúde Pública, 1993)
Results of an investigation carried out into a population of 285 dentists in Cordoba City (Cordoba, Argentine) with a view to evaluating their pharmacological knowledge, prescriptive behaviour and proposals for the improvement of drug usage, are described. This study showed that 58.3% of the dentists surveyed get most of their pharmacological and therapeutic information through published material issued by pharmacochemical labs. At the same time, about one-third of the individuals surveyed either did not answer or gave incorrect answers to questions related to the pharmacotherapeutic effects the antimicrobial or anti-inflammatory analgesics of their preference. Although 63.5% of the dentists said that they had taken the essential drug model reference list issued by the social security system into account, many of the drugs selected as preferences were not to be found on it. Regarding anti-microbial or anti-inflammatory analgesic drugs, the brands most frequently prescribed were the more expensive ones, strongh 66.5% of the dentists surveyed stated the contrary. Finally, this investigation revealed that five manufacturers together held a concentration of the anti-microbial and antiinflammatory analgesics prescribed by 83.7% and 82.4% of the dentists consulted respectively.